2015
DOI: 10.1002/jmrs.129
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive radiation therapy for bladder cancer: a review of adaptive techniques used in clinical practice

Abstract: Significant changes in the shape, size and position of the bladder during radiotherapy (RT) treatment for bladder cancer have been correlated with high local failure rates; typically due to geographical misses. To account for this, large margins are added around the target volumes in conventional RT; however, this increases the volume of healthy tissue irradiation. The availability of cone beam computed tomography (CBCT) has not only allowed in‐room volumetric imaging of the bladder, but also the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
12
0
8
Order By: Relevance
“…These offline ART studies demonstrate a reduction in normal tissue irradiated, and indicated the potential for considerably reduced target volumes. 76,77 The disadvantage of any offline techniques is that they only correct for the systematic differences in bladder position and volume.…”
Section: Bladdermentioning
confidence: 99%
See 1 more Smart Citation
“…These offline ART studies demonstrate a reduction in normal tissue irradiated, and indicated the potential for considerably reduced target volumes. 76,77 The disadvantage of any offline techniques is that they only correct for the systematic differences in bladder position and volume.…”
Section: Bladdermentioning
confidence: 99%
“…Kibrom et al reviewed offline ART studies for bladder cancer. 76 Of particular interest are the review of four composite volume offline ART techniques-in general, a composite volume technique uses the first few CBCTs to create composite target volumes for the offline adaptive plan. These offline ART studies demonstrate a reduction in normal tissue irradiated, and indicated the potential for considerably reduced target volumes.…”
Section: Bladdermentioning
confidence: 99%
“…Radiation is a major intervention in treating pelvic organ malignancies. However, the risk for developing complications such as radiation cystitis limits the radiation dose . The consequences of radiotherapy include a dose‐dependent detrimental effect on normal organ function within the irradiated field …”
Section: Introductionmentioning
confidence: 99%
“…The unpredictable variations in bladder volume due to intra-and inter-fractional filling during treatment have been evidently documented in bladder radiotherapy [2]. Large treatment planning margins are often used to ensure coverage and minimise geographical miss, however this also led to unnecessary irradiation vast areas of normal tissue [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer is the second most common urological cancer [4]. In order to strike a balance between local control and longterm toxicity for the bladder cancer patients, it is essential that the bladder target volume is covered adequately by high radiation dose whilst sparing the surrounding healthy tissue as much as possible [3]. This facilitated the development of adaptive techniques in bladder radiotherapy.…”
Section: Introductionmentioning
confidence: 99%